EXPERIMENTAL RESEARCH OF CHANGES IN PROOXIDANT-ANTIOXIDANT STATUS IN RATS IN CONDITIONS HIPERMELATONINEMIYA - Гільмутдінова М. Ш. (World of Medicine and Biology, 2012)
The impact of melatonin in conditions of hipermelatoninemia for determination of its influence on skeletal muscles (for example, the quadriceps muscle of rats) and prooxidant-antioxidant system are presented in the article.